Getting at the core of the common core with social studies - Turner, Thomas N.; Clabough, Jeremiah; Cole, William (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
The Common Core Standards have recently been adopted in most states across the nation and teachers are in the process of getting to the core of these standards. Teaching to standards is not a new concept; teachers have adapted to new standards every few years for quite some time. And teachers are adaptable, as can be seen in this book. We are writing this book to demonstrate how teachers use research-based strategies to meet Common Core Standards while still focusing on students. Our goal is to help teachers visualize students in action as other teachers describe the implementation of research-based strategies in their own classrooms, show student work samples, and provide reflections of student success in achieving the standards. Many Common Core Standards books focus on the standards, but our approach focuses on strategies that engage the students in the classroom--showing how different teachers at varying grade levels have used the strategies to meet the standards. With this focus, we believe that teachers gain a new and positive perspective on approaching the new standards and see the flexibility of strategies for meeting standards across subject areas.We have examined research on the strategies with the purpose of giving teachers a brief description of why these strategies work before giving actual examples from classrooms. We also work closely with teachers in the public schools and have our finger on the pulse of what is happening in the public schools--one of the current stressors being unpacking the Common Core StandardsThis book actually focuses on practice. We begin by laying out a rationale in our first chapter---The Core Value(s) of Education. Then, each chapter focuses on a strategy, including 1) a brief description about the research supporting each strategy and 2) several examples from different grade levels, which include a description of how the strategy was used, student work samples, and a reflection on the use of the strategy. The research descriptions are fairly short because, while we believe professional educators (aka teachers, in this case) should know the research that supports practice, we know they are not typically interested in long diatribes about the research.
Keywords: Social sciences -- Study and teaching (Elementary) -- United States.; Social sciences -- Study and teaching (Secondary) -- United States.; Social sciences -- Study and teaching -- Standards -- United States.; Education -- Multicultural Education.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books